PELAYANAN KURSUS PRA-NIKAH DI KUA KECAMATAN CICANTAYAN KABUPATEN SUKABUMI: PRE-MARITAL COURSE SERVICE IN STATE OFFICE OF RELIGIOUS AFFAIRS IN CICANTAYAN DISTRICT OF SUKABUMI REGENCY - M Agus Noorbani (Balai Penelitian dan Pengembangan Agama Jakarta, 2015)
The Government of Indonesia through the Ministry of Religious Affairs has issued a regulation regarding pre-marital course. The purpose of the issuance of this regulation is to raise the understanding and the knowledge about the life of the household/family in creating a family which is tranquility (sakinah), love (mawaddah) and mercy (rahmah) as well as reducing the number of disputes, divorces and domestic violences. Using observation and interview methods in data collection, this study aims to examine the process of implementation of pre-marital course referring to the Director General of Islamic Community Guidance (Dirjen Bimas Islam) Regulation No. DJ.II/542 in 2013. The study finds that pre-marital courses in Sukabumi regency has not been run in accordance with the regulations issued by Director General of Islamic Community Guidance (Dirjen Bimas Islam). Limited funding and lack of cross-ministerial cooperation have obstructed the implementation of pre-marriage courses programs. Keywords: Pre-marital courses, Weddings, Family, Islamic community guidance Pemerintah Indonesia melalui Kementerian Agama telah mengeluarkan peraturan mengenai kursus pra-nikah. Tujuan dikeluarkannya peraturan ini adalah untuk meningkatkan pemahaman dan pengetahuan tentang kehidupan rumah tangga/keluarga dalam mewujudkan keluarga yang sakinah, mawaddah, dan rahmah serta mengurangi angka perselisihan, perceraian, dan kekerasan dalam rumah tangga. Menggunakan metode pengamatan (observasi) langsung dan wawancara dalam pengumpulan data. Penelitian ini bertujuan untuk menelaah proses pelaksanaan kursus pra-nikah yang mengacu pada Peraturan Dirjen Bimas Islam Nomor DJ.II/542 Tahun 2013. Penelitian ini mendapati, bahwa kursus pra- nikah di Kabupaten Sukabumi belum berjalan sesuai dengan peraturan yang diterbitkan Peraturan Dirjen Bimas Islam Nomor DJ.II/542 Tahun 2013. Pembiayaan yang terbatas dan belum adanya kerja sama lintas kementerian menjadi kendala terlaksananya program kursus pra-nikah ini. Kata Kunci: kursus pra-nikah, pernikahan, keluarga, Bimas Islam